1997
DOI: 10.1016/s0886-3350(97)80210-6
|View full text |Cite
|
Sign up to set email alerts
|

Silicone oil adhesion to intraocular lenses: An experimental study comparing various biomaterials

Abstract: Although a silicone IOL shows maximal adherence to silicone oil, other lens biomaterials are not immune to this complication. Silicone oil coverage was related to the dispersive energy component of the surface charge of the IOL biomaterial. Low dispersive energy materials had less silicone oil coverage, while those with higher dispersive energy had more oil coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
9

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 15 publications
2
48
1
9
Order By: Relevance
“…[1][2][3][4][5] It is wellestablished that silicone oil manifests as a thick coating with droplet formation on the silicone IOL surface and adheres to the surface so tenaciously that it cannot be removed by instruments or injection of ophthalmic viscosurgical devices (OVDs). 1 The mean silicone oil coverage of silicone IOL optics varies between 80% 5 and 100%.…”
Section: J Cataract Refract Surg 2007; 33:127-129 Q 2007 Ascrs and Escrsmentioning
confidence: 99%
“…[1][2][3][4][5] It is wellestablished that silicone oil manifests as a thick coating with droplet formation on the silicone IOL surface and adheres to the surface so tenaciously that it cannot be removed by instruments or injection of ophthalmic viscosurgical devices (OVDs). 1 The mean silicone oil coverage of silicone IOL optics varies between 80% 5 and 100%.…”
Section: J Cataract Refract Surg 2007; 33:127-129 Q 2007 Ascrs and Escrsmentioning
confidence: 99%
“…[30][31][32][33][34][35] Apple and associates 30,31,34,35 in three different studies have compared the degree of silicone oil adherence occurring with several IOLs fabricated from various biomaterials. These studies from our laboratory have demonstrated that the more hydrophobic materials with higher dispersive energy and relatively higher contact angles had more silicone oil adherence.…”
Section: Silicone Oil Interaction With Different Iol Materialsmentioning
confidence: 99%
“…These studies from our laboratory have demonstrated that the more hydrophobic materials with higher dispersive energy and relatively higher contact angles had more silicone oil adherence. 30,31 Hydrophilic biomaterial with relatively low contact angles and low dispersive surface energy demonstrated less silicone oil adherence. Silicone oil coverage of poly (methyl methacrylate) (PMMA) IOLs was found to be significantly decreased once the latter were heparinsurface-modified (HSM).…”
Section: Silicone Oil Interaction With Different Iol Materialsmentioning
confidence: 99%
“…Apple et al [23]performed an in vitro experimental study comparing the degree of silicone oil adherence to various rigid and foldable IOL designs and also to the human lens capsule. Seven IOL styles comprising various biomaterials were studied: fluorine-treated (Fluorlens), HSM, hydrogel, Memory-Lens, PMMA, soft acrylic, and silicone lenses.…”
Section: Discussionmentioning
confidence: 99%
“…In several clinical and experimental studies, the interaction of silicone oil with various IOLs has been investigated [19, 20, 21, 22, 23]. In most of these studies, one type of silicone oil was used.…”
Section: Introductionmentioning
confidence: 99%